Systematic Review and Meta-Analysis of Thromboprophylaxis with Heparins Following Intracerebral Hemorrhage - Chi, Gerald; Lee, Jane J.; Sheng, Shi; Marszalek, Jolanta; Chuang, Michael L. (Thrombosis and Haemostasis, 2022)
Background The efficacy and safety of pharmacological thromboprophylaxis in patients with intracerebral hemorrhage (ICH) remains unclear.Methods A literature search was performed to collect studies comparing the effect of thromboprophylaxis in patients with ICH. The primary endpoints were deep vein thrombosis (DVT), pulmonary embolism (PE), and hematoma expansion or rebleeding. A meta-analytic approach was employed to estimate the relative risk (RR) by fitting fixed-effects (FE) and random-effects (RE) models.Results A total of 28 studies representing 3,697 hospitalized patients with ICH were included. Thromboprophylaxis was initiated within 4 days following hospital presentation and continued for 10 to 14 days in most of studies. Compared with control, thromboprophylaxis was associated with a reduced risk of DVT (47/1,399 [3.4%] vs. 202/1,377 [14.7%]; FE: RR, 0.24; 95% CI, 0.18–0.32; RE: RR, 0.27; 95% CI, 0.19–0.39) as well as PE (9/953 [0.9%] vs. 37/864 [4.3%]; FE: RR, 0.33; 95% CI, 0.19–0.57; RE: RR, 0.37; 95% CI, 0.21–0.66). Thromboprophylaxis was not associated with increased risk of hematoma expansion or rebleeding (32/1,319 [2.4%] vs. 37/1,301 [2.8%]; FE: RR, 0.75; 95% CI, 0.48–1.18; RE: RR, 0.80; 95% CI, 0.49–1.30) or mortality (117/925 [12.6%] vs. 139/904 [15.4%]; FE: RR, 0.82; 95% CI, 0.65–1.03; RE: RR, 0.83; 95% CI, 0.66–1.04).Conclusion Thromboprophylaxis was effective in preventing DVT and PE without increasing the risk of hematoma expansion or bleeding among ICH patients. Future studies should explore the long-term effects of thromboprophylaxis in this population, particularly on the functional outcomes.
Keywords: intracerebral hemorrhage; hemorrhagic stroke; pulmonary embolism; heparin